Monte Carlo simulation for the very anticipated detection of charged giants proteins in type-2 diabetes patients based on the internet of bio-nano things - Nieto Chaupis, Huber (2017)
An interesting application of the prospective technology called Internet of Bio-Nano Things (IoBNT) is in the territory of the medicine. It's expected that this technology plays the role as tool of surveillance of the functionalities of the human organs. To accomplish that, the deployment of nanodevices very near to organs should be a must. However, the idea to deploy nanodevices should be sustained in basis of basic processes, as the ones of physics for instance. In this paper, a physics model based on electrodynamics describing all those processes of anomalous fluxing of albumin in the very beginning of the diabetes kidney disease (DKD), and tested with the assistance of the Monte Carlo method is presented. According to the simulations, signal can be identified in those scenarios where is assumed that the nanosensor has the capabilities to defeat noise or background substantially. For these studies, we have associated an error of simulation of order of 15%.